Lipid droplets as multifunctional organelles related to the mechanism of evasion during mycobacterial infection - Almeida, Patrícia Elaine de; Pereira de Sousa, Núbia Maria; Rampinelli, Pollianne Garbero; Silva, Renata Vieira de Sousa; Correa, José Raimundo; D’Avila, Heloisa (Frontiers in Cellular and Infection Microbiology, 2023)
Tuberculosis (TB) is an infectious disease caused by the bacteria of the Mycobaterium tuberculosis (Mtb) complex. The modulation of the lipid metabolism has been implicated in the immune response regulation, including the formation of lipid droplets (LD)s, LD-phagosome association and eicosanoid synthesis. Mtb, M. bovis BCG and other pathogenic mycobacteria, as well as wall components, such as LAM, can induce LDs formation in a mechanism involving surface receptors, for instance TLRs, CD36, CD14, CD11b/CD18 and others. In addition, the activation of the lipid-activated nuclear receptor PPARγ is involved in the mechanisms of LD biogenesis, as well as in the modulation of the synthesis of lipid mediators. In infected cells, LDs are sites of compartmentalized prostaglandin E2 synthesis involved in macrophage deactivation, bacterial replication and regulation of the host cytokine profile. LDs also have a function in vesicle traffic during infection. Rab7 and RILP, but not Rab5, are located on LDs of infected macrophages, suggesting that LDs and phagosomes could exchange essential proteins for phagosomal maturation, interfering in mycobacterial survival. The pharmacological inhibition of LDs biogenesis affects the bacterial replication and the synthesis of lipid mediators and cytokines, suggesting that LDs may be new targets for antimicrobial therapies. However, it is still controversial if the accumulation of LDs favors the mycobacterial survival acting as an escape mechanism, or promotes the host resistance to infection. Thus, in this mini-review we discuss recent advances in understanding the important role of LDs in the course of infections and the implications for the pathophysiology of mycobacteriosis.